Evaluation of Body Weight and Body Measurements of Lesser-known Gang-Fatehpuri Sheep of Uttar Pradesh, India - Verma, Manoj K.; Singh, Vindhyavashini K.; Singh, Jaswant; Verma, Ajeet K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was aimed to evaluate morphometric characteristics of lambs of less known native sheep of Gang-Fatehpuri of Fatehpur  district of Uttar Pradesh during different growth stages in its breeding tract for breed recognition and registration with NBAGR, Karnal,  India. A total of 365 lambs of either sex of different age groups (94, 102, 95, and 74 heads of 3, 6, 9, and 12 months of age, respectively)  were surveyed in 15 villages of Fatehpur district. The overall values of body weight and body measurements, viz., body length, height  at withers, chest girth, tail length, and ear length recorded at 12 months of age (sexual maturity) were 29.62 ± 0.46 kg, 73.47 ± 0.46 cm,  73.54 ± 0.51 cm, 77.63 ± 0.43 cm, 40.08 ± 0.23 cm, and 18.29 ± 0.13 cm, respectively. The mean values of all the traits, except ear length,  of male lambs, were significantly (p
Keywords: Body measurements; Body-weight; Gang-Fatehpuri; Mutton type breed